Receding horizon maneuver generation for automated highway driving - Nilsson, Julia; Falcone, Paolo; Ali, Mohammad; Sjöberg, Jonas (Control engineering practice, 2015)
This paper focuses on the problem of decision-making and control in an autonomous driving application for highways. By considering the decision-making and control problem as an obstacle avoidance path planning problem, the paper proposes a novel approach to path planning, which exploits the structured environment of one-way roads. As such, the obstacle avoidance path planning problem is formulated as a convex optimization problem within a receding horizon control framework, as the minimization of the deviation from a desired velocity and lane, subject to a set of constraints introduced to avoid collision with surrounding vehicles, stay within the road boundaries, and abide the physical limitations of the vehicle dynamics. The ability of the proposed approach to generate appropriate traffic dependent maneuvers is demonstrated in simulations concerning traffic scenarios on a two-lane, one-way road with one and two surrounding vehicles. [Display omitted] •Formulation of affine collision avoidance constraints.•Simultaneous optimization of lateral and longitudinal control signals.•Receding horizon MPC decision-making and path planning problem formulated as a QP.